A photoredox catalysed Heck reaction via hole transfer from a Ru(II)-bis(terpyridine) complex to graphene oxide - Rosenthal, Marta; Lindner, Jörg K N; Gerstmann, Uwe; Meier, Armin; Schmidt, W Gero; Wilhelm, René (Royal Society of Chemistry)

A systematic literature review of model-driven security engineering for cyber–physical systems - Geismann, Johannes; Bodden, Eric (Journal of Systems and Software)

Explaining Static Analysis with Rule Graphs - Nguyen Quang Do, Lisa; Bodden, Eric (IEEE Transactions on Software Engineering)

PASAPTO: Policy-aware Security and Performance Trade-off Analysis - Computation on Encrypted Data with Restricted Leakage - Fischer, Andreas; Janneck, Jonas; Kussmaul, Jörn; Krätzschmar, Nikolas; Kerschbaum, Florian; Bodden, Eric (2020 IEEE Computer Security Foundations Symposium (CSF))

Heaps'n Leaks: How Heap Snapshots Improve Android Taint Analysis - Benz, Manuel; Krogh Kristensen, Erik; Luo, Linghui; P. Borges Jr., Nataniel; Bodden, Eric; Zeller, Andreas (International Conference for Software Engineering (ICSE))

Computation on Encrypted Data using Dataflow Authentication - Fischer, Andreas; Fuhry, Benny; Kerschbaum, Florian; Bodden, Eric (Privacy Enhancing Technologies Symposium (PETS/PoPETS))

CogniCrypt_GEN - Generating Code for the Secure Usage of Crypto APIs - Krüger, Stefan; Ali, Karim; Bodden, Eric (International Symposium on Code Generation and Optimization (CGO))

CogniCrypt -- The Secure Integration of Cryptographic Software - Krüger, Stefan
Frühere Studien haben empirisch offenbart, dass Fehlbenutzungen von kryptographischen APIs in Softwareanwendungen weitverbreitet sind. Dies geschieht vor allem, weil Software-Entwickler_innen aufgrund schlechten API-Designs und fehlenden Kryptographiewissens Probleme bekommen, wenn sie versuchen kryptographische Features zu implementieren. Die Literatur liefert mehrere Ansätze und Vorschläge diese Probleme zu lösen, aber alle scheitern schlussendlich auf die eine oder andere Weise daran die Anforderungen der Entwickler_innenzu erfüllen. Das Resultat ist eine insgesamt lückenhafte Landschaft verschiedener nur wenigkomplementärer Ansätze.In dieser Arbeit adressieren wir das Problem kryptographischer Fehlbenutzungen systematischer durch CogniCrypt. CogniCrypt integriert verschiedene Arten von Tool Supportin einen gemeinsamen Ansatz, der Entwickler_innen davon befreit wissen zu müssen, wie diese APIs benutzt werden müssen. Zentral für unseren Ansatz ist CrySL, eine Beschreibungssprache,die die kognitive Lücke zwischen Kryptographie-Expert_innen und Software-Entwickler_innenüberbrückt. CrySL ermöglicht es Kryptographie-Expert_innen zu spezifizeren, wie die APIs,die sie bereitstellen, richtig benutzt werden. Wir haben einen Compiler für CrySL implementiert, der es erlaubt auf CrySL-Spezifikationen aufbauenden Tool Support zu entwickeln. Wir haben weiterhin die statische Analyse CogniCrypt_SAST und den Code-Generator CogniCrypt_GEN entwickelt. Schlussendlich haben wir CogniCrypt prototypisch implementiert und diesen Prototyp in einem kontrollierten Experiment evaluiert.

Model-driven engineering and usability evaluation of self-adaptive user interfaces - Yigitbas, Enes (ACM SIGWEB Newsletter)

Cutting through the Jungle: Disambiguating Model-based Traceability Terminology - Holtmann, Jörg; Steghofer, Jan-Philipp; Rath, Michael; Schmelter, David (2020 IEEE 28th International Requirements Engineering Conference (RE))
Traceability, a classic requirements engineering topic, is increasingly used in the context of model-based engineering. However, researchers and practitioners lack a concise terminology to discuss aspects of requirements traceability in situations in which engineers heavily rely on models and model-based engineering. While others have previously surveyed the domain, no one has so far provided a clear, unambiguous set of terms that can be used to discuss traceability in such a context. We therefore set out to cut a path through the jungle of terminology for model-based traceability, ground it in established terminology from requirements engineering, and derive an unambiguous set of relevant terms. We also map the terminology used in existing primary and secondary studies to our taxonomy to show differences and commonalities. The contribution of this paper is thus a terminology for model-based traceability that allows requirements engineers and engineers working with models to unambiguously discuss their joint traceability efforts.

Scenario-based Specification of Security Protocols and Transformation to Security Model Checkers - Koch, Thorsten; Dziwok, Stefan; Holtmann, Jörg; Bodden, Eric (ACM/IEEE 23rd International Conference on Model Driven Engineering Languages and Systems (MODELS ’20))

Model-Driven Information Flow Security Engineering for Cyber-Physical Systems - Gerking, Christopher

Simulationsbasierte Betriebsfestigkeitsanalyse stanzgenieteter Bauteile - Otroshi, Mortaza; Meschut, Gerson; Masendorf, Lukas; Esderts, Alfons

GEMINI-Modellierungssprache für Wertschöpfungssysteme - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

GEMINI-Geschäftsmodellmuster-Kartenset - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodellvalidierung - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodell-Roadmapping - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Nanoantennas embedded in zinc oxide for second harmonic generation enhancement - Volmert, Ruth; Weber, Nils; Meier, Cedrik (Journal of Applied Physics)
Plasmonic nanoantennas for visible and infrared radiation strongly improve the interaction of light with the matter on the nanoscale due to their strong near-field enhancement. In this study, we investigate a double-resonant plasmonic nanoantenna, which makes use of plasmonic field enhancement, enhanced outcoupling of second harmonic light, and resonant lattice effects. Using this design, we demonstrate how the efficiency of second harmonic generation can be increased significantly by fully embedding the nanoantennas into nonlinear dielectric material ZnO, instead of placing them on the surface. Investigating two different processes, we found that the best fabrication route is embedding the gold nanoantennas in ZnO using an MBE overgrowth process where a thin ZnO layer was deposited on nanoantennas fabricated on a ZnO substrate. In addition, second harmonic generation measurements show that the embedding leads to an enhancement compared to the emission of nanoantennas placed on the ZnO substrate surface. These promising results facilitate further research to determine the influence of the periodicity of the nanoantenna arrangement of the resulting SHG signal.

Offenzeit plasmaaktivierter Polymeroberflächen für robuste klebtechnische Prozesse – OffPlas - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson; Stepanov, Sergey; Stalling, Annika; Ihde, Jörg; Mayer, Bernd (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Analyse und Vorhersage rezeptur- und zeitabhängiger Enthaftungserscheinungen geklebter SMC-Bauteile - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson (20. Kolloquium Gemeinsame Forschung in der Klebtechnik)